2022
DOI: 10.1111/polp.12460
|View full text |Cite
|
Sign up to set email alerts
|

Social networks of independents and partisans: Are independents a moderating force?

Abstract: While scholars have long recognized that social networks impact political engagement for partisans, comparatively little work has examined the role of networks for independent voters. In this article, we contribute to existing research on social networks and politics by surveying Arizona registered voters about their political persuasion, personal networks, and media consumption habits. Our findings show that independents have networks that are structurally different from partisans. Specifically, we found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 60 publications
(121 reference statements)
0
9
0
Order By: Relevance
“…Although prior studies often excluded pure Independents from their analyses (e.g., Abramowitz and Saunders 2006;Webster and Abramowitz 2017), studies including these individuals suggest their attitudes and behaviors are increasingly important to the electorate. Reilly and Hedberg (2022), for example, found Independents (which they classified as partisan-leaning Independents and pure Independents) have less politically homogeneous social networks, Democrats/Republicans are more likely to discuss politics with Independents than counter partisans, and that Independents are less likely to cut ties with Democrats/Republicans following a political dispute. With regard to elections, Independents tend to be more interested in presidential elections than midterms and less interested amidst elite polarization, but may be more affected by changes in the political context than other partisans (Miller et al 2022).…”
Section: Ideology and Independentsmentioning
confidence: 99%
“…Although prior studies often excluded pure Independents from their analyses (e.g., Abramowitz and Saunders 2006;Webster and Abramowitz 2017), studies including these individuals suggest their attitudes and behaviors are increasingly important to the electorate. Reilly and Hedberg (2022), for example, found Independents (which they classified as partisan-leaning Independents and pure Independents) have less politically homogeneous social networks, Democrats/Republicans are more likely to discuss politics with Independents than counter partisans, and that Independents are less likely to cut ties with Democrats/Republicans following a political dispute. With regard to elections, Independents tend to be more interested in presidential elections than midterms and less interested amidst elite polarization, but may be more affected by changes in the political context than other partisans (Miller et al 2022).…”
Section: Ideology and Independentsmentioning
confidence: 99%
“…political moderates who do not affiliate with a political party) is different from those of Democrats and Republicans. As expected, both Democrats and Republicans were most likely to talk about politics with those from their own political party, but compared to Democrats, Republicans were more willing and likely to have discussions with their politically independent friends (Reilly and Hedberg, 2022). Similarly, research has shown that Republicans tended to have more positive interpersonal relations with political independents, more so than did Democrats (Gastil et al, 2008;Hout and Fischer, 2002).…”
Section: Theoretical Backgroundmentioning
confidence: 51%
“…This proposed asymmetry in how liberals and conservatives perceive political moderates is supported by political science research on the personal beliefs and interaction patterns among political moderates, liberals and conservatives (Gastil et al, 2008;Hout and Fischer, 2002;Reilly and Hedberg, 2022). For example, Reilly and Hedberg (2022) compared the social networks of political moderates with those of liberals and conservatives and found that the social network structure of political independents (i.e.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This resulted in a significant reduction in the number of self‐described independents. Reilly and Hedberg (2022) have argued that in light of the more recent work of Klar and Krupnikov (2016) and Zschirnt (2011), which showed the importance of the independent identity, classifying self‐identified independents as partisans seems counterproductive in examining their influence on partisans, especially when respondents elected to self‐identify as leaners. The authors collapsed three groups—respondents who selected option 3, 4, or 5—as independent, thus treating leaners as Independents (VCF0303, Summary 3‐category scale).…”
Section: Discussionmentioning
confidence: 99%